Admissibility of using electronic media when informing residents about the intended local referendum in the commune (Discourse of Law and Administration, 2024)
Conducting a local referendum at the application of residents in a commune requires that the referendum initiator fulfill a number of requirements, including providing residents with information about the intended referendum in a manner customary in a commune. In recent years, a dispute has arisen as to whether information about the intention to hold a municipal referendum can be transmitted via electronic media, for example popular social sites, because these communication channels were increasingly used in practice by the initiators of municipal referendum. They were convinced that it was permissible and meets the requirements specified in the Local Referendum Act. The other side of this dispute – the bodies verifying residents’ applications – claimed that such action was contrary to the law. The subject of the study is to find an answer to the question which position in this dispute should be considered correct and implemented the will of the legislator.
Keywords: commune; local referendum; residents’ application; informing about the intended local referendum; electronic media